Predictors of Firm Performance and Supply Chain: Evidence from Indonesian Pharmaceuticals Industry - Asrini Asrini; Musnaini Musnaini; Yuni Setyawati; Lely Kumalawati; Nur Alifah Fajariyah (International Journal of Supply Chain Management, 2020)
Abstract- The recent trend in big data application has led the organizations to think about its application. Having in mind the importance of supply chain integration and learning the current study has attempted to explore the drivers of firm performance from the supply chain perspective. Data were collected from the employees working in the pharmaceuticals companies in Indonesia. Smart-PLS was used for data analysis. The results of the study showed that there is strong significant positive relationship between big data analytical capability and firm performance. Further the results also revealed a significant influence of supply chain integration and learning on the firm performance. The results also revealed supply chain agility as a significant positive mediator between the relationships of supply chain integration, big data analytical capability, learning and firm performance. All the hypothesis were accepted.